A review on the production of renewable aviation fuels from the gasification of biomass and residual wastes - Shahabuddin, M.; Alam, Md Tanvir; Krishna, Bhavya B.; Bhaskar, Thallada; Perkins, Greg (Bioresource technology, 2020)
•Review of conventional and emerging gasification technologies.•Summary of syngas cleaning and conditioning for FT synthesis.•Catalyst and reactor technologies for Fischer-Tropsch.•Overview of waste to aviation fuel projects. This article reviews the production of renewable aviation fuels from biomass and residual wastes using gasification followed by syngas conditioning and Fischer-Tropsch catalytic synthesis. The challenges involved with gasifying wastes are discussed along with a summary of conventional and emerging gasification technologies. The techniques for conditioning syngas including removal of particulate matter, tars, sulphur, carbon dioxide, compounds of nitrogen, chlorine and alkali metals are reported. Recent developments in Fischer-Tropsch synthesis, such as new catalyst formulations are described alongside reactor technologies for producing renewable aviation fuels. The energy efficiency and capital cost of converting biomass and residual wastes to aviation fuels are major barriers to widespread adoption. Therefore, further development of advanced technologies will be critical for the aviation industry to achieve their stated greenhouse gas reduction targets by 2050.